PENERAPAN DIGITAL MARKETING DAN BRANDING PRODUK PADA KOPERASI TENUN PANDAI SIKEK DI KECAMATAN X KOTO KABUPATEN TANAH DATAR - Rahmi Eka Putri; Laela Susdiani; Ricky Akbar (Jurnal Hilirisasi IPTEKS, 2021)
This Community Service activity is carried out at the Pandai Sikek Weaving Cooperative located in Nagari Pandai Sikek, X Koto District, Tanah Datar Regency. This activity aims to provide assistance in managing digital marketing and product branding at the Pandai Sikek Weaving Cooperative to members of the cooperative who are weavers from Nagari Pandai Sikek. Products are marketed in the form of woven cloth typical of Pandai Sikek and some handicrafts typical of West Sumatra. The Pandai Sikek Weaving Cooperative currently does not have a name and logo for the product being marketed, so the product does not have an identity that can be recognized by the public. The method used in this activity is brainstorming with activity partners to obtain the same thoughts about product names and logos. In addition, the implementation method is also in the form of training and assistance in managing digital marketing as one of the product marketing strategies. In this activity, product branding has been produced with the name "Songket Weaving Pandai Sikek." With this name and logo, it is hoped that the products of the Pandai Sikek Weaving Cooperative can be immediately recognized by consumers, who will impact increasing product sales. In addition, this Community Service activity also provides assistance to partners in digital marketing management to market products both in marketplaces such as Tokopedia and on social media such as Instagram and Facebook. With this digital marketing, the products of the Pandai Sikek Weaving Cooperative have been marketed more widely, not only in the area of origin and surrounding areas but also to reach consumers from other regions in Indonesia.